Telemedicine's Impact on Diabetes Care During the COVID‐19 Pandemic: A Cohort Study in a Large Integrated Healthcare System - Reysha Patel; Jie Huang; Loretta Hsueh; Anjali Gopalan; Andrea Millman; Isabelle Franklin; Mary Reed (Journal of Diabetes)
ABSTRACT Aims To examine whether patients exposed to primary care telemedicine (telephone or video) early in the COVID‐19 pandemic had higher rates of downstream HbA1c measurement and improved HbA1c levels in the second year of the pandemic. Methods In a cohort of 242,848 Kaiser Permanente Northern California patients with diabetes, we examined associations between early‐pandemic patient‐initiated telemedicine visits and downstream HbA1c monitoring and results during the second year of the pandemic. Results Adjusted HbA1c measurement rates were significantly higher among patients with telemedicine exposure in the early‐pandemic prior year than those with no visits in the prior year (91.0% testing for patients with video visits, 90.5% for telephone visits, visits, 86.7% for no visits, p < 0.05). Among those with HbA1c measured, the rates of having an HbA1c < 8% in the second year of the COVID‐19 pandemic were also statistically significantly higher among patients with telemedicine exposure in the early‐pandemic prior year than those with no visits in the prior year (68.5% with HbA1c < 8% for video visits, 67.3% for telephone visits, 66.6% for no visits, p < 0.05). Conclusions Access to telephone and video telemedicine throughout the early COVID‐19 pandemic was associated with patients' continued engagement in recommended diabetes care. Although our study analyzed telemedicine use during a pandemic, telemedicine visits may continue to support ongoing health care access and positive clinical outcomes.